Influence of Pulse Waveform and Frequency on Evoked Torque, Stimulation Efficiency, and Discomfort in Healthy Subjects. (February 2021) - Rabello, Rodrigo; Fröhlich, Matias; Maffiuletti, Nicola Angelo; Vaz, Marco Aurélio
Abstract : Objective: The aim of the study was to determine the influence of neuromuscular electrical stimulation pulse waveform and frequency on evoked torque, stimulation efficiency, and discomfort at two neuromuscular electrical stimulation levels. Design: This is a repeated measures study. The quadriceps muscle of 24 healthy men was stimulated at submaximal (neuromuscular electrical stimulationsub ) and maximal (neuromuscular electrical stimulationmax ) levels using two pulse waveforms (symmetrical, asymmetrical) and three pulse frequencies (60, 80, 100 Hz). Repeated measures analysis of variance and effect sizes were used to verify the effect of pulse waveform and pulse frequency on stimulation efficiency (evoked torque/current intensity) and discomfort and to assess the magnitude of the differences, respectively. Results: Stimulation efficiency was higher for symmetrical (neuromuscular electrical stimulationsub = 0.88 ± 0.21 Nm/mA; neuromuscular electrical stimulationmax = 1.27 ± 0.46 Nm/mA) compared with asymmetrical (neuromuscular electrical stimulationsub = 0.77 ± 0.21 Nm/mA; neuromuscular electrical stimulationmax = 1.02 ± 0.34 Nm/mA; P ⩽ 0.001; effect size = 0.56–0.66) but did not significantly differ between frequencies ( P = 0.17). At both neuromuscular electrical stimulation levels, there were no statistically significant differences in discomfort between pulse waveforms or frequencies. Conclusions: The higher stimulation efficiency of symmetrical pulses suggests that this waveform would be preferred to asymmetrical pulses in clinical practice. Stimulation frequencies between 60 and 100 Hz can be used interchangeably because of similar efficiency and discomfort. Abstract : Supplemental digital content is available in the text.